If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-y+z = 1
y^4*((6*y^9)/3) = 0
2;3;1;1;0;3
-9/5-(2/3) = -3/2
(3*z)/10 = 1
| 3x+6+2x=7x-7+9 | | 3a(2-5)-2(a+2)=29 | | 4y+3-y+7=31 | | 6y^9/3y^4 | | 3w+6-w=2w-2+9 | | 6x-15=5x-2x | | 2ln(9x)=8 | | -3(x-5)-2x=5 | | 2x+4+4x+7=x | | -8(7n+7)+1=2n+3 | | -9/5-2/3=-3/2 | | -4y+6=23x-3 | | 5v-6=-36 | | 3z/10=1 | | 30kx-6kx=8 | | 26-x=15 | | 3.3m-4-3.3m-7= | | 5+2(3x-2)=13 | | -2(x+4)=-10 | | A^2+B^2=1156 | | 2y+4+-15y+3y+-6= | | 14n+6p-8n=18p | | 5m+2(m-5)=17 | | -2=2+2w | | 4(8-x)+36=92-2(3x+24) | | 3kx+24=9kx | | 3x+34=-28 | | 5w+14=89 | | 67.2=6(m+2.6) | | 2x+5=8x-18 | | 8=3v-16 | | 9x+1+7x+9=180 |